Why Did I Lose My Seat in the United States Congressional Elections? You Didn‘t Advertise Online Enough! - Milan Školník; Michael Haman; Anna Marie Nešpůrková (Acta Politologica)
In this paper, we examine campaign spending on Facebook during the 2020 U.S. congressional elections. We draw conclusions based on data from the Federal Election Commission and the Facebook Ad Library. This is one of the first articles on this topic. We point out and show how this data differs and how other researchers should treat it. Specifically, we focus on U.S. Democratic congresspeople who lost elections. Indeed, during the Democratic Party debate, voices were raised that its progressive wing was to blame for the loss of seats; in contrast, Rep. Alexandria Ocasio-Cortez, a rising star of the wing, argued that the lack of Facebook advertising was a factor in why seats were lost. The article concludes that the really well-known Democratic figures who lost the elections spent very little on Facebook ads compared to Ocasio-Cortez. We also compare Republican opponents with Democrats. In addition, we highlight how the Ocasio-Cortez campaign and the others differed with respect to the timing of campaign spending and the targeting of Facebook ads to specific states. Further, we compare data regarding campaigns available through the Federal Election Commission and Facebook and underscore the importance of the transparency of the Facebook Ad Library.